Treatment of essential varicose veins of the lower limbs - Amorin Cal, Raul (Cirugía del Uruguay, 1971)
1) Therapy of essential varicose veins should be aimed fundamentally at the "elimination of outward flow points" and secondarily, at the elimination of trunks. This means prior identification of all "outward flow" and their treatment in one single surgical operation. 2) The technique which seems to offer best results is safenous stripping, elimination of collateral varicose veins and ligation of communicants in their place. The plans should proceed along rigurous tactics and techniques. Periodic post-operatory observation should be insisted upon. Surgery-sclerosis association is evaluated. 3) "Nosologic" and "topographic" diagnosis of varicose veins is studied as a basis for deciding on the therapy to be applied. The paper contains a brief analysis of the hemodynamic effects of varicose veins. 4) Anatomic, clinical and therapeutic aspects of the territories of the small and great safenous, communicants and extrapelvic branches of the internal iliac vein, are studied, and an analysis is made of the technical aspects of each case. A procedure for the extirpation of varicose collateral veins is described. 5) The importance of the participation of communicating veins in the venous pathology of the lower limb is stressed, since insufficiency thereof may also be considered, or may seem, "essential", as is the case of the safenas. 6) An analysis is made of residual, persistent or recurrent varicose veins, resulting from erroneous diagnosis or treatment, or a combination of both.